The effect of a single loaded-particle on bubble pinch-off dynamics in various liquids. (2nd February 2023) - Chen, Shixing; Xu, Enle; Meng, Xianliang; Wu, Guoguang; Jiang, Xiaofeng
Graphical abstract: Highlights: The particle effect on bubble pinch-off in various liquids was investigated; particle adhering to the bubble neck hinders the pinch-off; particle adhering to the upper/bottom part of the bubble neck promotes the pinch-off; The shear-thinning property of non-Newtonian fluid enhances the pinch-off; Bubble deformation was affected by loaded particle and liquid properties. Abstract: Particle-laden interface especially particle-loaded gas–liquid interface widely exists in actual applications of gas–liquid-solid multiphase flow. This study reported the pinch-off dynamics and initial deformation of a bubble loaded with a particle in various liquids. The relative size and position between bubble and particle, and liquid properties, jointly affect the pinch-off dynamics. If the particle locates in the bubble neck region (PLB-n), the pinch-off process is hindered, and the exponent ( b  = 0.6 − 0.67) is higher than that of pure bubble, while if the particle is on the upper or bottom part of the bubble neck (PLB-u/PLB-b), it promotes the pinch-off process and leads to a lower exponent ( b  = 0.4 − 0.5) compared to the pure bubble. In addition, at the initial stage after pinch-off, both the loaded-particle and the liquid properties affect the gas–liquid interface deformation and bubble-particle relative motion.